Morphological traits in maize cultivars at varied N and Mg fertilization rates - Szulc, Piotr; Nowosad, Kamila; Bocianowski, Jan (Polish Journal of Agronomy, 2016)
Field experiments were conducted at the Teaching and Experimental Station in Swadzim near Poznań in the years 2009- 2011. They were carried out in the split-split-plot design with three experimental factors in four replications. Analyses were conducted to investigate four nitrogen fertilization rates and two magnesium fertilization rates on morphological traits of plants and ears in two types of maize cultivars differing in their genetic profiles. The aim of the conducted field tests was the evaluation of the effect of application of magnesium in maize cultivation, which would increase effectiveness of nitrogen fertilization. A visible symptom of that may be a modification of morphological features of the plant. The properties analyzed in this paper (plant height) can have significant effect on shaping plant photosynthetic surface area that determines productivity. It was shown that the number of plants was inversely proportional to the applied nitrogen rate. The stay-green hybrid was characterised by a greater number of plants both after emergence and during harvest. The significantly shortest plants were found for the dose of 0 kg N ha-1 in comparison to three other levels of application of this ingredient, for which the value of this property was significantly at the same level. Regardless of the nitrogen and magnesium dose, the „staygreen” ES Paroli variety was characterized by shorter plants, a lower height of ear setting, a shorter length and diameter of the ears and the smaller volume of a ears compared with the ES Palazzo hybrid. Under conditions of this study it was ineffective to apply magnesium, as evidenced by the lack of effect of this macroelement on the analysed traits.